Cultivation of nine varieties of watermelon under edaphoclimatic conditions of the Brazilian Savannah: Morphological variables, physicochemical characteristics and useful life of fruits - Soares da Silva, Edgley (2020)
Refrigeration is necessary to preserve the quality of watermelon fruits for longer, however, this technology is difficult to access and costly. Therefore, it is necessary to look for alternatives such as the selection of new varieties of watermelon that present good resistance to transport, superior fruit quality and high postharvest shelf life. In this context, the objective in this work was to evaluate the morphological, physicochemical and shelf life characteristics of the fruits of nine varieties of watermelon. It was conducted through a randomized complete block experimental design in a subdivided plot scheme. Nine varieties of watermelon were evaluated in the plots: Explorer, Magnum, Santa Amelia, Top Gun, Crimson Sweet, Electra, PX 397, Charleston Gray and Jubilee, and in the subplots five storage times: 0; 5; 10; 15 and 20 days. The edaphoclimatic conditions of the Amazon Savannah in Roraima, Brazil, favor the morphological, physicochemical characteristics and shelf life of the fruits of the Explore, Santa Amelia and Crimson Sweet varieties. The fruits of the watermelon varieties quickly lose their quality and are not suitable for in nature consumption after 15 days of storage at ambient temperature and relative humidity in the Amazon Savannah of Roraima, Brazil, since the content of ° Brix after this period is less than 9 °. The new studies related to the subject must consider the acceptance of the consumer market of the varieties with the greatest potential obtained.